Monetary Child Poverty Analysis in Indonesia: Empirical Evidence with Panel Data - Abdul, Irawati; Hasan, Yusrin S.; Akib, Fitri Hadi Yulia (Yayasan Riset dan Pengembangan Intelektual, 2024)
The monetary child poverty gap in Indonesia shows significant disparities between provinces, especially in eastern Indonesia. This phenomenon hinders the achievement of SDGs and has implications for the quality of long-term human development. This study aims to analyze the factors that influence the level of monetary child poverty in Indonesia using panel data from 34 provinces for the period 2019-2022. The analysis method uses panel data regression with the Fixed Effect Model (FEM) approach, based on secondary data from BPS, by analyzing eleven covariates to identify significant determinants of monetary child poverty. The estimation results show five variables that have a significant effect: birth certificate ownership, internet use for school, Human Development Index, regional economic growth, and labor force participation. Meanwhile, the variables of child labor, Gini ratio, out-of-school rate for 7-12 year olds, preschool level, and PIP recipients at elementary and junior high school levels do not show a significant effect. These findings imply the need for an integrated reformulation of child poverty alleviation policies, focusing on strengthening the population administration system, digital transformation of education, improving the quality of human development, and optimizing inclusive economic growth.